2018
DOI: 10.2298/fil1818353d
|View full text |Cite
|
Sign up to set email alerts
|

Equitable list vertex colourability and arboricity of grids

Abstract: A graph G is equitably k-list arborable if for any k-uniform list assignment L, there is an equitable L-colouring of G whose each colour class induces an acyclic graph. The smallest number k admitting such a coloring is named equitable list vertex arboricity and is denoted by ρ = l (G). Zhang in 2016 posed the conjecture that if k ≥ ⌈(∆(G) + 1)/2⌉ then G is equitably k-list arborable. We give some new tools that are helpful in determining values of k for which a general graph is equitably k-list arborable. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The first statement of Theorem 1 generalizes the result obtained in [3] for d ∈ {1, 2}. In this paper we present an algorithm that confirms both, the first and second statements of Theorem 1 for all possible d. The algorithm, given in Sect.…”
Section: Motivation and Preliminariessupporting
confidence: 73%
“…The first statement of Theorem 1 generalizes the result obtained in [3] for d ∈ {1, 2}. In this paper we present an algorithm that confirms both, the first and second statements of Theorem 1 for all possible d. The algorithm, given in Sect.…”
Section: Motivation and Preliminariessupporting
confidence: 73%
“…In [13] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [25], series-parallel graphs [23], graphs with small maximum average degree [3], certain graphs related to grids [4], powers of cycles [10], and certain planar graphs (see [2,14,24] and [26]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [12]).…”
Section: Equitable Choosabilitymentioning
confidence: 90%
“…We verify this stronger version of Zhang's Conjecture for powers of paths, 2-degenerate graphs, and certain other graphs. We also show that if G is equitably k-list arborable it does not necessarily follow that G is equitably (k + 1)-list arborable which addresses a question of Drgas-Burchardt, Furmańczyk, and Sidorowicz (2018).…”
mentioning
confidence: 84%
“…Indeed, K 9,9 is equitably vertex 2-arborable, but it is not equitably vertex 3-arborable. The following conjecture of Wu, Zhang, and Li is well-known and has received some attention in the literature (see e.g., [6,23,26,29,30,31,32]).…”
Section: List Vertex Arboricity and Equitable Vertex Arboricitymentioning
confidence: 99%